Primer reporte de patogenicidad por nemátodos entomopatógenos sobre la chinche de los pastos Collaria scenica Stål (Hemiptera: Miridae) - Naranjo, Natalia [UNESP]; Montero, Daniel Antonio Villamil [UNESP]; Sáenz Aponte, Adriana (My University, 2011)
The study was aimed to test the pathogenicity of Steinernema sp. and Heterorhabditis sp. in Collaria scenica. The effect of different concentrations of infective juveniles (IJ) were tested on nymphs and adults of C. scenica. For this purpose, the bugs were inoculated with 5 000 JI of each nematode species in a factorial design (3x2), and seven concentrations were tested in a JI factorial design (7×2×2). The bugs showed 100 % mortality and symptoms of pathogenicity. Infection was found with both species of nematodes and penetration was assumed to be through the spiracles and anus. A higher capacity of pathogenicity was observed with Steinernema sp. Based on the results Heterorhabditis sp. and Steinernema sp. could constitute an efficient tool to control populations of C. scenica in pastures. © 2011, Sociedad Venezolana de Entomología.
First record of infection by entomopathogenic nematodes of the grass bug Collaria scenica Stål (Hemiptera: Miridae)
Keywords: Biological control; Heterorhabditis sp (SL0708); Infective juvenile; Pennisetum clandestinum; Steinernema sp